2019
DOI: 10.21815/jde.019.156
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Dental Hygienists About Thesis Completion in Graduate Education

Abstract: Few studies have been published on thesis completion experiences of master's degree students. However, for doctoral students, dissertation completion has been found to be dependent on individual, relational, and institutional factors. The aim of this study was to examine dental hygienists’ perceptions of their experiences completing a thesis as a requirement for an advanced degree. A qualitative phenomenological research design was used utilizing virtual focus groups with a national purposive sample of dental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 8 publications
1
4
0
2
Order By: Relevance
“…Our findings were consistent with the literature about the difficulties advisees had completing their thesis while simultaneously managing their other responsibilities and when coupled with their sense of self‐doubt, significantly contributed to their advisees’ diminished motivation 29,30 . Our findings and those of Coruth et al 29 identified these responsibilities played a crucial role in decreasing advisee's motivation and focus during their research.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our findings were consistent with the literature about the difficulties advisees had completing their thesis while simultaneously managing their other responsibilities and when coupled with their sense of self‐doubt, significantly contributed to their advisees’ diminished motivation 29,30 . Our findings and those of Coruth et al 29 identified these responsibilities played a crucial role in decreasing advisee's motivation and focus during their research.…”
Section: Discussionsupporting
confidence: 90%
“…The focus group members described methods of adapting advising techniques to meet the individual needs of each advisee to keep the thesis process progressing, which aligned with previous research citing organized communication and use of scaffolding to break the thesis process into "chunks" as an approach to pedagogy for research methods 10,13,28 . The use of scaffolding also addresses the need for structure and clear guidance by DH thesis students as reported by Coruth et al 30 …”
Section: Discussionmentioning
confidence: 67%
“…Nuestro estudio encontró que los graduados opinan que los procesos de la tesis no son claros y con la ejecución se aprende a sobrellevarlos, principalmente debido a una mala orientación ya sea por parte del asesor o de la institución; los hallazgos concuerdan con los estudios de Flynn et al 17 y Coruth et al 10 donde se encontró una limitada comprensión de los procesos por parte de higienistas dentales durante su posgrado. El análisis de las entrevistas de los grupos focales reveló un valor general del título profesional para continuar con los estudios de posgrado y obtener mejores oportunidades laborales.…”
Section: Discussionunclassified
“…La guía de entrevista estuvo conformada por preguntas de datos personales (sexo, edad, trabajo actual y tiempo de duración de la tesis) y cuatro preguntas basadas en el estudio de Coruth et al 10 : 1. ¿Cómo describiría su experiencia al completar la tesis?…”
Section: Conclusion Various Factors Influence the Completion Of The University Thesis Such Asunclassified
“…Theses follow the “apprenticeship” model where individual students are paired with one or several faculty members (i.e., thesis committee) who can guide the student through an independent written deliverable (Bruce et al, 2008). Though beneficial for independent student learning, this model of student training may delay the student’s time to degree completion (Bruce et al, 2008; Coruth et al, 2019; Skeith et al, 2018). Challenges may include delays or difficulties identifying an original and feasible thesis topic, securing faculty that can support their theses, and completing their theses in the intended timeframe for degree completion.…”
Section: Introductionmentioning
confidence: 99%